Menstrual Morbidities, Menstrual Hygiene, Cultural Practices during Menstruation, and WASH Practices at Schools in Adolescent Girls of North Karnataka, India: A Cross-Sectional Prospective Study - Rajasri G Yaliwal; Aruna M Biradar; Shreedevi S Kori; Subhash Chandra R. Mudanur; Shivakumar U Pujeri; Mohd Shahnnawaz (Wolters Kluwer Medknow Publications, 2020)
Background: Issues of menstrual morbidities, menstrual hygiene, and cultural practices are rarely discussed by adolescents. The burden of menstruation and cultural practices which the adolescent girls have to face has been less quantified. This study aims to assess the issues related to menstruation in school girls. Methods: A cross-sectional prospective study was conducted on 1016 school-going adolescent girls in January 2020. A questionnaire in English and in Kannada was distributed to girls of class 8-12 of ages between 10 and 19 years. Results: 70.5% of the girls attained menarche by 12 to 14.9 years, 37.2% of the girls had their periods every 28-34 days, and 12.2% of the girls said they have heavy periods. 61.95% of the girls had dysmenorrheal, and 9.7% of the girls said that they required medications for the pain. 70.7% of the girls were using commercial sanitary napkins, 12.7% were using cloth, and 15.3% were using both. 55.5% of the girls who were using cloth as an absorbent were not drying the cloth in sunlight. 57.1% of the girls were washing their genitals more than 2 times a day. 93.8% were having a bath during menses and 87.2% were using soap along with water. 37.7% of the girls disposed of their pads by burning them, 50.8% of then disposed them in the dust bin, and 4.9% of them buried them. 8.6% of the girls said that they remained completely absent from school during periods. 17.85% said that they remained absent for a day. 53.4% of the respondents said that they have dificulty in concentrating at school. 76.1% said that they had adequate water and sanitation facilities at school. 22.3% said that there was an adequate facility to change their pads at school. 73.2% said that they could get a spare pad at school. 43.3% of the girls said they avoided cultural functions during their periods, and 38.5% said that they avoided religious ceremonies and practices during their periods. 8.7% of the girls were made to sit outside the house during their periods. The girls from rural areas had poorer hygienic habits, in comparison to the urban girls. Cultural restrictions such as sitting outside the house during menstruation and restricting play were more in the rural girls than the urban girls. Conclusion: Menstrual morbidities, menstrual hygiene management, and cultural beliefs all play a role in school absenteeism in adolescent girls. Improvement of facilities at school and conducting awareness programs can help adolescent girls to attend schools.